Link between Metabolic Syndrome and Insulin Resistance - Gluvic, Zoran; Zaric, Bozidarka; Resanovic, Ivana; Obradovic, Milan; Mitrovic, Aleksandar; Radak, Djordje; R. Isenovic, Esma (Current Vascular Pharmacology, 2017)
Metabolic syndrome (MetS) is a leading public health and clinical challenge worldwide. MetS represents a group of interrelated risk factors that predict cardiovascular diseases (CVD) and diabetes mellitus (DM). Its prevalence ranges between 10 and 84%, depending on the geographic region, urban or rural environment, individual demographic characteristics of the population studied (sex, age, racial and ethnic origin), as well as the criteria used to define MetS. Persons with MetS have higher mortality rate when compared with people without MetS, primarily caused by progressive atherosclerosis, accelerated by pro-inflammatory and pro-coagulation components of MetS. Considering the high prevalence of metabolic disorders (glucose metabolism disorder, hypertension, dyslipidaemia, obesity etc.), preventive healthcare should focus on changing lifestyle in order to reduce obesity and increase physical activity. This narrative review considers the available evidence from clinical and experimental studies dealing with MetS, and current treatment options for patients with insulin resistance and MetS.
Keywords: insulin resistance